Respuesta a la aplicacion de nematicida en banano en la zona de Uraba, Colombia - Castillo Ruái, J.D.=700 1 Araya Vargas, M.; Patiño Hoyos, L.F.
(Es, En)
Ilus., 51 ref.
Keywords: MUSA; HELYCOTILENCHUS MULTICINCTUS; RODOPHOLUS SIMILIS; NEMATODOS DE LAS PLANTAS; CONTROL DE NEMATODOS; NEMATOCIDAS; COSTA RICA; MUSA AAA; MONONCHUS; AGRONOMIA MESOAMERICANA